2021
DOI: 10.1097/meg.0000000000002204
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis scores that can be used in follow-up of after direct-acting antiviral treatment: APRI, FIB-4, King score and GUCI

Abstract: Introduction Sustained virologic response in the treatment of chronic hepatitis C can be achieved with direct-acting antivirals (DAA) in recent years. Monitoring virologic and histologic response to treatment is essential and noninvasive methods are preferred. In our study, we aimed to determine the regression of fibrosis following DAA treatment with serum fibrosis indices constituting a noninvasive method. Method Patients with chronic hepatitis C to whom DAA treatment is started between January 2016 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Chronic hepatitis C and liver fibrosis the curve (AUC): 0.800 and 0.782] [9]. In our study, the highest value of area under the curve (AUC) in the ROC analysis performed for the cut-off point to predict the presence of histological fibrosis was calculated with the FIB-4 scoring (AUC: 0.763).…”
Section: R -Correlation Coefficient Hai -Histological Activity Indexmentioning
confidence: 69%
See 1 more Smart Citation
“…Chronic hepatitis C and liver fibrosis the curve (AUC): 0.800 and 0.782] [9]. In our study, the highest value of area under the curve (AUC) in the ROC analysis performed for the cut-off point to predict the presence of histological fibrosis was calculated with the FIB-4 scoring (AUC: 0.763).…”
Section: R -Correlation Coefficient Hai -Histological Activity Indexmentioning
confidence: 69%
“…In another study, a statistically significant decrease in APRI and FIB-4 scores was observed at the end of treatment, and at the 12 th and 24 th weeks after treatment compared to before treatment with DAA. A significant positive correlation was found between scores and biopsy results before treatment [area under the curve (AUC): 0.800 and 0.782] [ 9 ]. In our study, the highest value of area under the curve (AUC) in the ROC analysis performed for the cut-off point to predict the presence of histological fibrosis was calculated with the FIB-4 scoring (AUC: 0.763).…”
Section: Discussionmentioning
confidence: 99%
“…A research study completed between January 2016 and January 2018 reported that 91 subjects with hepatitis C had their liver biopsies done and, afterward, had their AAR, FIB-4, Göteborg University Cirrhosis Index (GUCI), and King’s scores measured. They showed a positive correlation with the histological findings and had a significant value of less than 0.001 [ 25 ]. However, in another study, patients to whom antiviral therapy was administered did not show very efficacious results nor a correlation between FIB-4 and APRI with a degree of fibrosis regression after therapy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although liver biopsy is recommended prior to antiviral treatment, it may cause complications and is limited by relatively high costs, meaning it is not typically used in the routine management of CHC patients receiving DAAs. To replace biopsy, several noninvasive tests have been created, which are reproducible, and validated in several published studies [ 35 , 36 ]. Accordingly, we applied TE to measure LSM, and GPR, FIB-4, and APRI scores to evaluate the degree of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%